2006
DOI: 10.1002/ejlt.200500290
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of long‐chain polyunsaturated fatty acids during deodorization of fish oil

Abstract: Long-chain polyunsaturated fatty acids (LC-PUFA) of the n-3 series, particularly eicosapentaenoic (EPA) and docosahexaenoic (DHA) acid, have specific activities especially in the functionality of the central nervous system. Due to the occurrence of numerous methylene-interrupted ethylenic double bonds, these fatty acids are very sensitive to air (oxygen) and temperature. Non-volatile degradation products, which include polymers, cyclic fatty acid monomers (CFAM) and geometrical isomers of EPA and DHA, were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 26 publications
2
104
1
1
Order By: Relevance
“…It is now well known that during deodorisation and/or refining of oil cistrans isomerisation reactions could have occurred [31,32]. Recent research has recommended that the deodorisation of marine oils should be conducted at a maximum temperature of 180°C to avoid geometrical isomerisation [33,34]. However the trans fatty acid isomers of EPA and DHA was not the subject of research in this study.…”
Section: Determination Of the Total Lipid And Moisture Contentsmentioning
confidence: 65%
“…It is now well known that during deodorisation and/or refining of oil cistrans isomerisation reactions could have occurred [31,32]. Recent research has recommended that the deodorisation of marine oils should be conducted at a maximum temperature of 180°C to avoid geometrical isomerisation [33,34]. However the trans fatty acid isomers of EPA and DHA was not the subject of research in this study.…”
Section: Determination Of the Total Lipid And Moisture Contentsmentioning
confidence: 65%
“…These FA isomers would contribute to the FT-NIR signal and influence the quantitation based on the FT-NIR model. It was previously shown that heating fish oil produces trans isomers of the highly unsaturated FA, particularly EPA and DHA, that could only be resolved using very long highly polar capillary columns [34][35][36]. Even though every effort is made to prevent and isolate these products during the production of n-3 PUFA, small amounts were confirmed using the 100 m column (Fig.…”
Section: Ft-nir Quantification Of Fatty Acidsmentioning
confidence: 96%
“…This method has some complications. For example: addition of acetyl chloride at room temperature generates an exothermic reaction that often results in loss of sample and possible injury to the analyst; adding the acetyl chloride slowly with stirring is often cumbersome for large numbers of samples; certain polyunsaturated fatty acids are less stable at temperatures of 100°C during the transesterification process; and the generation of molecular species that may contribute to the over-estimation of fatty acids [10]. Furthermore, the FID response varies with carbon-chain variation.…”
Section: Introductionmentioning
confidence: 99%